Stem Cutting Growth of Red Dragon Fruit (Hylocereus costaricensis) due to Aplication of Cow Manure and KCl in Andosol - Irfan Nofriandi; Faiz Barchia; Fahrurrozi Fahrurrozi; Bilman W. Simanihuruk; Entang Inoriah Sukarjo (TERRA : Journal of Land Restoration, 2021)
This study aims to obtain the optimum dose of manure for red dragon fruit plant growth on Andosol, optimum K fertilizer dose for red dragon fruit plant growth on Andosol, and the interaction of manure and K fertilizer for red dragon fruit plant growth on Andosol. This research was conducted from August 2018 to November 2018 at the Horticulture Seed Center, Kepahiang Regency, Bengkulu Province. This study used a completely randomized design (CRD) consisting of two factors with three replications. The first factor is cow manure, which is 0 g/polybag, 20 g/polybag, 40 g/ polybag, and 60 g/polybag. The second factor is K fertilizer, which is 0 g/polybag, 1.38 g/polybag, 2.76 g/polybag, and 5.52 g/polybag. The results showed that the application of cow manure with a dose of 60 g/polybag resulted in the best shoot growth time and shoot fresh weight